2011
DOI: 10.1681/asn.2010111196
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Attenuates Proteinuria and Kidney Injury

Abstract: Inhibitors of histone deacetylase (HDAC) have anti-inflammatory and antifibrotic effects in several organs and tissues, but their effect on the progression of renal disease is unknown. Here, we studied the effect of valproic acid in adriamycin-induced nephropathy in mice. Administration of valproic acid before kidney injury prevented the development of proteinuria and the onset of glomerulosclerosis. Even after postponing treatment until the peak of adriamycin-induced proteinuria, valproic acid rapidly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
91
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 53 publications
11
91
0
2
Order By: Relevance
“…[35][36][37][38] The mechanism is uncertain; however, it has been shown that epigenetic changes in interstitial fibroblasts obtained from fibrotic kidneys promote fibroblast activation that can be reversed using DNA methyltransferase inhibitors. 39 Because there is extensive crosstalk between histone modification and DNA methylation, 40 it is possible that histone hyperacetylation induced by m4PTB decreases fibrosis by reprogramming these fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] The mechanism is uncertain; however, it has been shown that epigenetic changes in interstitial fibroblasts obtained from fibrotic kidneys promote fibroblast activation that can be reversed using DNA methyltransferase inhibitors. 39 Because there is extensive crosstalk between histone modification and DNA methylation, 40 it is possible that histone hyperacetylation induced by m4PTB decreases fibrosis by reprogramming these fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…14) Recent studies reported that epigenetics, such as DNA methylation and histone modifications, play pivotal roles in the progression of CKD, and some inhibitors of histone deacetylase (HDAC) exert beneficial effects against CKD. [15][16][17] Moreover, the expression of EC-SOD is known to be regulated by epigenetics in human lung cancer cells, 18,19) monocytes/macrophages, 20) and retina endothelial cells 21) ; however, limited information is currently available on EC-SOD regulation mechanisms in CKD models and the involvement of epigenetics.…”
mentioning
confidence: 99%
“…The mechanism of action for VPA in the treatment of autoimmune diseases has yet to be identified. However, treatment of ADR nephropathy with VPA was found to increase glomerular H3K9 acetylation and decrease glomerular apoptosis [78].…”
Section: Selective Class I Inhibitorsmentioning
confidence: 94%
“…Furthermore, treatment of glomerulosclerosis in the adriamycin nephropathy mouse model with VPA reduced proteinuria in early phase renal disease [78]. VPA has been demonstrated to inhibit TNF-α, NF-κB, and IL-6 pathways, which have been shown to be dysregulated during many autoimmune diseases [78].…”
Section: Selective Class I Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation